Antineutrophilic Cytoplasmic Antibody Positive Vasculitis Associated with Methimazole Use. (28th April 2015) - Shikha, Deep; Harris, Jonathan; Resta, Christine; Park, Patricia
Abstract : ANCA-associated vasculitis (AAV) is a rare and potentially life threatening complication associated with antithyroid drug use. It is more commonly reported with propylthiouracil, with fewer cases reported with methimazole use. We present the case of a 55-year-old man with toxic multinodular goiter which was treated with methimazole for 6 months. He developed ANCA positive leukocytoclastic vasculitis with hemorrhagic and necrotic bullous lesions of lower extremities. The vasculitis was initially thought to be secondary to recent cephalosporin use; however, the skin lesions progressed despite stopping the cephalosporin and treatment with steroids, and he developed osteomyelitis. His vasculitis resolved after cessation of methimazole use. This case highlights the importance of careful monitoring for variable manifestations of AAV in patients treated with methimazole.